Mobilités et précarités : Lorenzo Da Ponte dans le monde de l’opéra (1779-1830) - David Do Paço (Diasporas: Circulations, Migrations, Histoire)
This article examines the relationship between geographical and social mobility in the erratic career of Lorenzo Da Ponte and the opera milieu of the 18th Century. It stresses the role of patronage on the attraction and circulation of authors and composers as well as exploring the existence of more or less institutionalised corporatist forms of solidarity responsible for regulating a market of word and music. Although a certain and necessary degree of complementarity, if not interdependence, can be seen amongst the authors, composers and actors, their mobility patterns differ as do the dynamics driving their various careers. Precarious conditions and employment thus generated a search for security which often entailed a change of social and professional status. In this way, mobility was neither circulatory nor necessarily positive; on the contrary it often highlighted precarious economic and social circumstances.